Penerapan Gaya Kepemimpinan Lurah Tuwung Dalam Menciptakan Budaya Kerja Yang Kondusif - Andi Muhammad Galif; Rabina Yunus; Ashar Prawitno (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2025)
This study aims to analyze the implementation of the village head’s leadership style in creating a conducive work culture at the Tuwung Village Office, Barru District, Barru Regency. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the Head of Tuwung Village applies a combination of consultative, participative, delegative, and directive leadership styles as proposed in Gatto’s Leadership Theory. However, participative and consultative leadership styles are the most dominant approaches in leading the organization. The consultative leadership style is reflected in the village head’s openness to receiving suggestions and input from staff members and the community before making decisions. Meanwhile, the participative leadership style is demonstrated through the involvement of staff and community members in decision-making processes, planning activities, and the implementation of development programs. In addition, the delegative leadership style is implemented by granting authority to staff members according to their respective duties and functions, while the directive leadership style is reflected in the village head’s role in providing direction, guidance, and making decisions on issues that require certainty and prompt action. The implementation of these leadership styles has contributed to effective communication, increased employee participation, strengthened organizational cooperation, and the development of a conducive work culture within the Tuwung Village Office.